THE EFFECT OF GREEN ACCOUNTING AND COMPANY SIZE ON COMPANY PERFORMANCE - Setiyaningsih, Rozi Fery; Kamaluddin, Nurhadi; Kartika, Fitri Dian; Alfian, Mohammad (Applied Accounting and Management Review (AAMAR), 2024)
This research aims to determine the effect of Green Accounting and Company Size on company performance. Using a quantitative approach. The sampling method is purposive sampling of secondary data on food and beverage sector companies listed on the Indonesia Stock Exchange. Process the data using Multiple Linear Regression with SPSS 26 software. The research results show that Green Accounting Disclosure has a significant positive effect on company performance. On the other hand, company size has a significant negative effect on company performance.